GAMBARAN DUKUNGAN NYATA KELUARGA PADA PASIEN RAWAT INAP KELAS III DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2018 - Putri Handayani; Lita; Susi Erianti (Jurnal Kesehatan Husada Gemilang, 2022)
Patients who are hospitalized are individuals who are having health problems. Various impacts can occur due to lack of support provided by the family, this is seen from the physical condition of the patients tends to long recovery and is affected to their psychological condition that cause mental disorders such as depression. According to the initial survey in the long-stay room class III of RSUD Arifin Achmad, Riau Province, to 10 patients’ families, 6 of them were to accompany the patients because they their selves could eat, drink, defecate, and urinate. This research was conducted with the aim to find out the picture and the support of the family in patients with sneaks.This is a descriptive quantitative research. The population of the research were all patients’ family, 127 people were the sample that were gained through the consecutive sampling. The instrument of the research were questionnaires and univariate analysis. The results demonstrate that there are 123 people (96.9%), 85 people (66.9%) did not help them to drink, 68 people (53.5%) did not help them to take medicine, 84 people (66.1%) helped them to prepare their food, 85 people (66.9%) helped them to urinate, 74 people (58.3%) helped them to defecate, 95 people (74.8%) did not help them to maintain cleanliness of their skin, teeth, and mouth, 97 people (76.4%) did not help them to replace their cloths, 85 people (66.9%) did not help them to clean their ears, 84 people (66.1%) did not help them to tidy up their hair, 76 people (59.8%) did not help them to take care of their body, 91 people (71.7%) did not help them walk to bathroom, 104 people (81.9%) did not help them to sit, 91 people (71.7%) did not help them move. It is highly expected that RSUD of Arifin Achmad is able to advance the quality of services and guide the patients’ family to support patients because it is very helpful so they can recover quickly.